Influence of Viscous Dissipation on MHD Non- Newtonian Fluid Past a Stretching Sheet with Suction/Injection - Shashidar Reddy Borra; K. Saritha (Technological Innovation in Engineering Research Vol. 3, 2022)
The present chapter describes the viscous dissipation effects on MHD Non-Newtonian fluid flow past a stretching surface along with suction/injection. The equations governing the flow field are solved numerically by employing implicit finite difference scheme and the results are scrutinized graphically for velocity and temperature fields. It is evident from the results that the magnetic field and suction parameter reduces the velocity of the fluid. The effect of velocity exponent is to increase the temperature of the fluid and increase in Eckert number if to raise the temperature.